2005
DOI: 10.1016/j.neuron.2005.09.019
|View full text |Cite
|
Sign up to set email alerts
|

glial cells missing and gcm2 Cell Autonomously Regulate Both Glial and Neuronal Development in the Visual System of Drosophila

Abstract: The transcription factors Glial cells missing (Gcm) and Gcm2 are known to play a crucial role in promoting glial-cell differentiation during Drosophila embryogenesis. Our findings reveal a central function for gcm genes in regulating neuronal development in the postembryonic visual system. We demonstrate that Gcm and Gcm2 are expressed in both glial and neuronal precursors within the optic lobe. Removal of gcm and gcm2 function shows that the two genes act redundantly and are required for the formation of a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
159
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(169 citation statements)
references
References 72 publications
9
159
1
Order By: Relevance
“…Eye-specific mosaic flies were generated by using ey 3.5 FLP; FRT40cycE AR95 ͞GlaBc in which the FLP recombinase was expressed under control of a retina-specific eyeless promotor fragment, and twinspots were eliminated by the recessive cell lethal cycE mutation (19,27). MARCM analyses on R1-R6 and lamina target neurons were performed as described by using the elavGAL4 transgene to drive expression of mCD8GFP (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye-specific mosaic flies were generated by using ey 3.5 FLP; FRT40cycE AR95 ͞GlaBc in which the FLP recombinase was expressed under control of a retina-specific eyeless promotor fragment, and twinspots were eliminated by the recessive cell lethal cycE mutation (19,27). MARCM analyses on R1-R6 and lamina target neurons were performed as described by using the elavGAL4 transgene to drive expression of mCD8GFP (12).…”
Section: Methodsmentioning
confidence: 99%
“…5 P-R). To confirm that these apparent differences in cellular requirement do not reflect differences in expressivity between Liprin-␣, LAR, and N-cadherin, we used the ''ELF'' system to generate target clones in which most target neurons are rendered homozygous mutant (27) and visualized the lamina of adult flies by using an R cell-specific marker (Fig. 5 D, I, N, and S).…”
Section: Liprin-␣ and Lar Are Not Required In Lamina Neurons For R Cementioning
confidence: 99%
“…To generate single mutant R7 axons with the MARCM system (Lee and Luo, 1999), flies were crossed to produce the following progeny: (1) hsFlp/ϩ; tutl 01085 , FRT40A/tub-GAL80, FRT40A; PanR7-GAL4, UAS-Synb-GFP/ϩ (flies were heat-shocked at 38°C for 1 h to induce mitotic recombination and were kept at 18°C to reduce background in wild-type cells); (2) GMR-Flp/ϩ; tutl 01085 , FRT40A/tub-GAL80, FRT40A; longGMR-GAL4, UAS-mCD8-GFP/ϩ; and (3) ey 3.5 -Flp/ϩ; tutl 01085 , FRT40A/tub-GAL80, FRT40A; longGMR-GAL4, UAS-mCD8-GFP/ϩ. To examine loss of tutl specifically in the target region, we used the ELF (ey-Gal80, lama-Ga14, UAS-FLP) system (Chotard et al, 2005) to generate ey 3.5 GAL80/ϩ; tutl 01085 , FRT40A/ubiGFP, cycE, FRT40A; lamaGAL4-UAS-Flp/ϩ progeny. tutl GAL4 was generated by jumping the GAL4 transgene on the C155 chromosome (X) to replace the P element in the tutl 01085 allele on the second chromosome using the P-element replacement method described previously (Sepp and Auld, 1999 23 by using the FLP/FRT-based strategy described previously (Parks et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Surface glia ensheath the brain and play a role in the formation of the blood-brain barrier. Cortex glia surround neurons and neuroblasts, while neuropile glia compartmentalize the neuropile, forming axon tracts for neurites (Chotard et al 2005;Pereanu et al 2005;Schwabe et al 2005). In addition, another subset of glia, the retinal basal glia, are born in the optic stalk and migrate into the eye imaginal disc (Choi and Benzer 1994;Rangarajan et al 1999).…”
mentioning
confidence: 99%
“…Thus, activation of loco is a critical step in glia differentiation. Recently, it has been shown that Gcm also functions to promote lamina neuron formation in the postembryonic larval nervous system (Chotard et al 2005;Soustelle and Giangrande 2007). Thus, other Gcm-independent mechanisms that regulate the activation of Pnt, Repo, and Loco and the suppression of neurogenic genes such as atonal, asense, and deadpan would be critical for glial specification and terminal differentiation.…”
mentioning
confidence: 99%